UDC 378.147:004.896:62 ENHANCING THE METHODOLOGY FOR APPLYING INTELLIGENT CONTROL SYSTEMS IN THE TEACHING OF TECHNICAL SCIENCES: Abdumananov Akhrorjon Adkhamjonovich, associate professor of the international medical university “Central Asian Medical University” - Abdumanonov, Axrorjon (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
This article analyzes the scientific and theoretical foundations, methodological approaches and socio-pedagogical necessity of using intelligent management systems (IMS) in teaching technical subjects. The integration of artificial intelligence, machine learning and digital analytics technologies into the educational process is shown as an important factor in increasing the effectiveness of teaching, creating individual educational trajectories and developing students' professional competence. The article discusses the state of implementation of IMS in the higher education system of Uzbekistan, existing problems and promising solutions.